2016
DOI: 10.7554/elife.15106
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic pruning in the female hippocampus is triggered at puberty by extrasynaptic GABAA receptors on dendritic spines

Abstract: Adolescent synaptic pruning is thought to enable optimal cognition because it is disrupted in certain neuropathologies, yet the initiator of this process is unknown. One factor not yet considered is the α4βδ GABAA receptor (GABAR), an extrasynaptic inhibitory receptor which first emerges on dendritic spines at puberty in female mice. Here we show that α4βδ GABARs trigger adolescent pruning. Spine density of CA1 hippocampal pyramidal cells decreased by half post-pubertally in female wild-type but not α4 KO mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

9
77
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(89 citation statements)
references
References 85 publications
9
77
1
Order By: Relevance
“…Thus, there has been recent interest in the mechanisms that underlie synaptic pruning which can involve microglia (Paolicelli et al, 2011) and autophagy (Tang et al, 2014), likely the final steps in the pruning process. Our recent findings (Afroz et al, 2016) suggest that adolescent synaptic pruning in the CA1 hippocampus of the female mouse is triggered by the tonic inhibition generated by α4βδ GABA A receptors (GABARs). These receptors emerge on the dendritic spine at the onset of puberty (Shen et al, 2010), identified by vaginal opening (typically ~PND 35), and remain at high levels for the next 10 days (Aoki et al, 2012).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, there has been recent interest in the mechanisms that underlie synaptic pruning which can involve microglia (Paolicelli et al, 2011) and autophagy (Tang et al, 2014), likely the final steps in the pruning process. Our recent findings (Afroz et al, 2016) suggest that adolescent synaptic pruning in the CA1 hippocampus of the female mouse is triggered by the tonic inhibition generated by α4βδ GABA A receptors (GABARs). These receptors emerge on the dendritic spine at the onset of puberty (Shen et al, 2010), identified by vaginal opening (typically ~PND 35), and remain at high levels for the next 10 days (Aoki et al, 2012).…”
mentioning
confidence: 99%
“…At puberty, α4βδ GABARs impair the activation of NMDA receptors (NMDARs) (Shen et al, 2010, Afroz et al, 2016) which are necessary for spine maintenance (Ultanir et al, 2007) via their regulation of spine proteins which stabilize the actin cytoskeleton (Afroz et al, 2016). This process produces the dramatic decrease in spine density during the pubertal period, based on results comparing wild-type with the α4−/− mouse (Afroz et al, 2016) which is also a functional δ knock-out (Sabaliauskas et al, 2012, Peng et al, 2014).…”
mentioning
confidence: 99%
See 3 more Smart Citations